Are Alternative Farmers Yielding Success with Online Marketing and Communication Tools for Their Social Capital and Business Viability? - Katie M. Abrams; Abigail Sackmann (Journal of Applied Communications, 2014)
To foster direct-to-consumer marketing, some alternative farmers are shifting to online tools like social media. What is unknown, however, is how they use them and what impacts use has on their business. The purpose of this study was to characterize and determine influences and outcomes of alternative farmers’ use of various online communication channels to better understand what they stand to gain (or lose) from participation in these activities as it relates to their farm business viability and social capital. Through survey data of 82 alternative farmers, it was learned their personal use of social media was highly correlated with their business use. Most of their time on the Internet was spent finding farming information and finding and interacting with customers; these activities (along with several others) were positively correlated with online bridging social capital. Personal uses of Facebook were indicative of greater social capital, whereas business uses of any social media were not. For business viability, the more Facebook Page likes their farms had, the more revenue they had, but no relationships were found between their business use of social media and customer loyalty or customer relationship. In sum, alternative farmers’ use of online communication tools was positively related to their social capital and their use of Facebook Pages was positively related to farm revenue. This study provides critical benchmark data to later determine the impact of effective use of these tools.
Keywords: Alternative farmers; online marketing; direct-to-consumer marketing